Parents' satisfaction with care in pediatric intensive care units - Cintia de Cassia Cintra; Pedro Celiny Ramos Garcia; Simone Brandi; Francielly Crestani; Alessandra Rodrigues Dias Lessa; Mariana Lucas da Rocha Cunha (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To verify the parents' satisfaction in relation to the care provided to their child admitted to the pediatric intensive care unit and associated clinical factors. Method: Exploratory, cross-sectional study, with a total of 84 parents, in a private hospital in Sao Paulo, Brazil. Data collection took place from March 2019 to January 2020, in the post-discharge period. Data were analyzed using descriptive statistics and Spearman's Correlation Coefficient. Results: Mean satisfaction was high (5.75) (SD=0.35). There was no correlation between parents' satisfaction and length of hospital stay, severity and illness. Conclusion: Parents showed high levels of satisfaction with the care received in pediatric intensive care, regardless of disease classification, length of hospital stay or severity. Greater satisfaction was observed in the domains of professional attitude, care and cure, information and parents' participation.